ADJEKTIVA BAHASA NAMLA - Sitti Mariati (Balai Bahasa Provinsi Papua, 2019)
Namla language is one of many languages in Papua which has a small number of native speakers. This language is spoken by Namla tribe, in Namla village, Senggi District, Keerom, Papua. Namla language has several word classes, like most other languages around the world. One of this class is adjective. In this article, adjective in Namla based upon the same word class in Bahasa Indonesia from its semantically behavior. There are two main types of adjective, there are, stratified adjective and non-stratified adjective. stratified adjective states a quality of noun, consist of (1) adjective of characteristic, (2) adjective of size, (3) adjective of colour, (4) adjective of time/age, (5) adjective of distance, (6) adjective of emotions, and (7) adjective of senses/touches. Non-stratified adjective states a membership of a noun in a group.